Toward peptide-based bioelectronics: reductionist design of conductive pili mimetics. Issue 2 (25th May 2018) - Guterman, Tom; Gazit, Ehud
Proteins and peptides possess inherent properties which can benefit medical devices that interact with electro-responsive tissues. However, proteinaceous materials are typically electrically insulating and hence are not suitable to be utilized as conductive elements in electromedical and other bio-interfacing devices. The discovery of intrinsic electrical conductivity in bacterial protein nanofibers, termed e-pili, could give rise to mimetic reductionist design and thus provide an opportunity to improve the function of existing electromedical devices. In this Special Report we review key aspects concerning the properties of e-pili and present the ongoing effort toward the design of mimetic conductive nanostructures. We highlight the advantages of using self-assembling peptides as building blocks for this purpose and discuss the prospect of the envisioned mimetic nanostructures.